Long-term results of neoadjuvant chemoradiotherapy using cisplatin and 5-fluorouracil followed by esophagectomy for resectable, locally advanced esophageal squamous cell carcinoma - Murakami, Yuji (J Radiat Res, 2018)
This study retrospectively evaluated the long-term results of neoadjuvant chemoradiotherapy (NCRT) followed by esophagectomy for the patients with resectable, locally advanced esophageal squamous cell carcinoma (ESCC). Altogether, 49 patients treated from 2008 to 2012 were analyzed. Chemotherapy consisted of 5-fluorouracil and cisplatin. Radiotherapy was performed with a total dose of 40 Gy in 20 fractions for primary tumor, metastatic lymph nodes, and elective nodal area. Subsequently, transthoracic esophagectomy with extensive lymphadenectomy was performed. The median follow-up time for the survivors was 86 (range, 55–111) months. Pathological complete response from NCRT was observed in 17 (35%) patients. The 5-year overall survival and relapse-free survival rates were 56% [95% confidence interval (CI): 43–71%] and 55% (95% CI: 41–69%), respectively. The 5-year locoregional control rate was 84% (95% CI: 74–95%). Multivariate analyses revealed body mass index, N-factor, and %ΔSUVmax as significant factors for overall survival. Recurrences and within–irradiation field failure were observed in 16 (31%) and 4 (8%) patients, respectively. Toxicities of NCRT were generally mild. Postoperative Grade IIIb or worse complications were seen in 14% of patients, including one Grade V case (2%). The 5-year incidence rate of late complications of Grade 3 or worse was 22% (95% CI: 7–36%). The cumulative 5-year incidence rate of metachronous malignancies was 13% (95% CI: 1–26%). NCRT followed by esophagectomy for patients with resectable, locally advanced ESCC showed favorable locoregional control and overall survival, with acceptable postoperative complications. Long-term careful follow-up for late complications and metachronous malignancies is needed.